Physiotherapeutic management of acute ankle sprains : a survey of clinical practice in the Western Cape and comparison thereof to evidence based guidelines - Simpson, Helene (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScPhysio)--Stellenbosch University, 2013.